Analysis of lunar pyroclastic deposit FeO abundances by LRO Diviner - Allen, C; Greenhagen, B; Donaldson Hanna, K; Paige, D (American Geophysical Union, 2012)
[1] Thermal infrared reflectance spectra of rock‐forming minerals include a prominent minimum near 8μm, known as the “Christiansen feature” (CF). The inflection point wavelength is sensitive to the degree of polymerization of silicates, which is strongly influenced by major cations – notably iron – in the minerals. Laboratory spectra of lunar soils demonstrate that the CF location is closely correlated to the sample's bulk FeO abundance, across the full range of Apollo soil samples, including pyroclastic glass. This correlation is the basis for estimating lunar surface FeO abundances using orbital thermal infrared measurements. The Diviner Lunar Radiometer Experiment on the Lunar Reconnaissance Orbiter includes three thermal infrared channels, selected to determine the CF positions for sites across the lunar surface. Diviner measurements are used to derive FeO abundances in the Aristarchus, Sulpicius Gallus, and Rima Fresnel pyroclastic deposits. The calculated FeO abundances for Aristarchus and Sulpicius Gallus lie within the compositional range of FeO‐rich pyroclastic glasses but outside the range of most mare soils, supporting the interpretations of these deposits as glass rich. The calculated FeO abundance for the Rima Fresnel deposit is close to that of mare soils, supporting a contention that this deposit is dominated by basaltic fragments rather than glass. The Diviner measurements hold the potential to determine FeO abundances in many lunar pyroclastic deposits. A better understanding of these compositions will provide insight into the magmatic history and composition of the lunar interior, as well as an enhanced inventory of potential resources for future human exploration.